Special conditions relating to preventive measures applied to minors - Dache, Florina Lăcrămioara (Technium Social Sciences Journal, 2023)
At national level but also European, The minor person is represented by those under the age of 18. For all of them, in case of necessity of criminal liability, a series of measures are applied that are classified as special. Thus to be criminally liable, the minor must be over the age of 14, and for the interval of 14 to 16 years, In order to decide on criminal liability, it is necessary to resort to a forensic expertise. At the same time, regardless of the acts committed by the minor , a He cannot be detained like an adult and cannot serve a sentence in a maximum security prison. The new Code of Criminal Procedure regulates these matters through Article 243, aspects that are of a special nature regarding the application of preventive measures to minors. Thus, It is expressly provided that preventive measures shall be ordered against the minor defendant in the same way as the legislation provided for adults however, with certain derogations and additions, they are intended to provide the defendant with additional protection due to age. In 1865, Upon the entry into force of the First Romanian Penal Code, We identify regulations on special treatment of minors, which are found in Title IV which was entitled "On Cases Defending Punishment or Reducing Punishment". The current foundations of criminal regulations regarding minors were laid with the criminal code of 1968, regulating for the first time criminal liability, educational measures and punishments. Although the foundations of this special legislation were laid decades ago, this topic continues to be topical and in continuous modification and legislation, due to the intervention of the European Union, which tries to continuously align the laws with the current situations.